Postharvest Losses, Food Safety and Value Chains of select Fruits and Vegetables in the Philippines: A Review of Literature - Bayogan, E. V.; Secretaria, L. B.; Sampiano, K. F. S. (International Food Policy Research Institute, 2022)
This report produced by FRESH Initiative partner Applied Horticultural Institute, in coordination with University of the Philippines Mindanao, provides an overview of the literature on several aspects of fruit and vegetable value chains in the Philippines; such as postharvest losses and its root causes, common postharvest practices for specific crops, government policies and practices that mitigate postharvest losses, food safety issues and their prevalence in the Philippines, as well as recommendations for future research or interventions.